Genetic dissection of value-added quality traits and agronomic parameters through genome-wide association mapping in bread wheat (T. aestivum L.) - Vishwakarma, Manish K.; Bhati, Pradeep K.; Kumar, Uttam; Singh, Ravi P.; Kumar, Sundeep; Govindan, Velu; Mavi, Gurvinder Singh; Thiyagarajan, Karthikeyan; Dhar, Narain; Joshi, Arun K. (Frontiers in Plant Science, 2024)
Bread wheat (T. aestivum) is one of the world's most widely consumed cereals. Since micronutrient deficiencies are becoming more common among people whose primality depends upon cereal-based diets, a need for better-quality wheat varieties has been felt. An association panel of 154 T. aestivum lines was evaluated for quality traits: Grain Appearance (GA) Score, grain Hardness (GH), Phenol Reaction (PR) Score, Protein percent, SDS Sedimentation Value, and Test Weight (TWt). In addition, the panel was also phenotyped for grain yield and related traits such as days to heading, days to maturity, Plant height, and thousand kernel weight for the year 2017-18 at BISA Ludhiana and Jabalpur sites. We performed a genome-wide association analysis on this panel using 18,351 genotyping-by-sequencing (GBS) markers to find marker-trait associations for quality and grain yield-related traits. We detected 55 SNP MTAs for qualityrelated traits on chromosomes 7B (10), 1A (9), 2A (8), 3B (6), 2B (5), 7A (4), 1B (3), 3A, 4A, 6D, having two and rest of the other 4B, 5A, 5B, and 1D have one each. Additionally, 20 SNP MTA was detected for yieldrelated traits based on field experiment conducted in Ludhiana on 7D (4) and 4D (3) chromosomes, while 44 SNP MTAs were reported for Jabalpur on chromosomes 2D (6), and 7A (5), 2A (4), and 4A (4).Utilizing these loci in marker-assisted selection will benefit from further validation studies for these loci to improve hexaploid wheat for better yield and grain quality.